The Executive Career Guide for MBAs: Inside Advice on Getting to the Top from Today's Business Leaders - Richard H. Beatty; Nicholas C. Burkholder (New York(State): John Wiley & Sons, 1996)
The first part of the book is based on extensive international surveys and in-depth interviews with more than 3,000 senior executives and placement directors at dozens of top firms - including Johnson & Johnson, the Vanguard Group, Motorola, and Coca-Cola - as well as with the deans of such prestigious schools as Stanford, Wharton, and MIT/Sloan Graduate School of Management. In the second part of the book, the authors show you how to apply what you$1 (Bve learned. A complete, step-by-step guide to conducting a successful executive job search, it coaches you in the skills you need to identify and land jobs that will be important stepping-stones in your rise to the top. You learn both the traditional and most recent techniques for flushing out the best job opportunities. And you get a gold mine of expert tips, tricks, and detailed guidelines on how to write powerful resumes and cover letters, and how to ace an interview, along with dozens of sample resumes and cover letters, interview check-lists, sample dialogues, and more.s
(NP(B/14876, (NP(B/14451s
Keywords: strategies -- business -- successful career -- job